Use of an aerial reconnaissance model during the movement of oversized loads. (October 2020) - Drozd, Jan; Neubauer, Jiří
The paper sets out the results of an experiment carried out using the Virtual Battle Space 2 simulator to verify the applicability of an autonomous unmanned aerial system (UAS) reconnaissance model when moving oversized loads. The model is originally implemented within a decision-support system under military conditions. The aim of the experiment is to verify the possibilities of using the model for civilian needs. The basic output of the experiment presented in the paper is confirmation that the autonomous UAS reconnaissance model can be applied in the actual transportation of oversized loads: the experiment confirms the author's hypothesis. Based on the result of the experiment it is possible to state that a slightly modified UAS model can significantly influence the execution phase of the oversized load movement in a positive way. It shows that the use of the model reduces the time of the movement and avoids unexpected interferences.